2017
DOI: 10.1177/1078155217702213
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of toxicities in acute myeloid leukemia patients with and without renal impairment treated with decitabine

Abstract: Purpose There are limited data regarding the clinical use of decitabine for the treatment of acute myeloid leukemia in patients with a serum creatinine of 2 mg/dL or greater. Methods We retrospectively evaluated 111 patients with acute myeloid leukemia who had been treated with decitabine and compared the development of toxicities during cycle 1 in those with normal renal function (creatinine clearance greater than or equal to 60 mL/min) to those with renal dysfunction (creatinine clearance less than 60 mL/min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…As a specific DNA methyltransferase (DNMT) inhibitor, DCA can induce the differentiation of tumor cells into normal cells and tumor cell apoptosis by reversing the DNA methylation process 5 . The mechanism involved in DCA resistance in TNBC is complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a specific DNA methyltransferase (DNMT) inhibitor, DCA can induce the differentiation of tumor cells into normal cells and tumor cell apoptosis by reversing the DNA methylation process 5 . The mechanism involved in DCA resistance in TNBC is complex.…”
Section: Discussionmentioning
confidence: 99%
“…As a specific DNA methyltransferase (DNMT) inhibitor, DCA can induce the differentiation of tumor cells into normal cells and tumor cell apoptosis by reversing the DNA methylation process. 5 The mechanism involved in DCA resistance in TNBC is complex. Our previous studies showed that miR-155 is upregulated in TNBC, but whether miR-155 is involved in stemness and DCA resistance in BC has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, some data on cardiac disorders associated with AZA such as atrial fibrillation and pleuro‐pericardial effusion were retrieved (see Table ), but with a frequency below 5%. Furthermore, data about the occurrence of CF in patients treated with AZA are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…reported a case of rapid heart failure in a patient treated with capecitabine, a pyrimidine analogue of AZA . Cardiac toxicity was also observed in patients treated with decitabine, another hypomethylating agent . An immune reaction or dose‐dependent toxicity have also been suggested as a possible mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective study of 111 patients with AML treated with decitabine showed a higher incidence of cardiotoxic side effects in patients with renal dysfunction. New onset heart failure was noted only in patients with renal dysfunction [ 15 ]. Our patient developed cardiac dysfunction despite normal kidney function.…”
Section: Discussionmentioning
confidence: 99%